Estrategias neuroeducativas para el mejoramiento del déficit atencional más hiperactividad (TDAH) en los niños y niñas de educación inicial, en la Unidad Educativa María Tapia de Velasco, de la parroquia urbana de Guanujo, del cantón Guaranda, provincia Bolívar, periodo 2018 – 2019 - Pilco Purcachi, Franco Junior (2019)
This document shows a process of analysis and development of a frame of reference, for the elaboration and implementation of "NEUROEDUCATIONAL STRATEGIES FOR THE IMPROVEMENT OF THE ATTENTIONAL DEFICIT MORE HYPERACTIVITY ADHD IN CHILDREN AND GIRLS OF INITIAL EDUCATION IN THE EDUCATIONAL UNIT MARÍA TAPIA DE VELASCO OF THE URBAN PARISH OF GUANUJO DEL CANTÓN GUARANDA, BOLIVAR PROVINCE, PERIOD 2018 - 2019", Which aims to deepen the knowledge of Attention Deficit Hyperactivity Disorder (ADHD) in children. In it, the proposal is investigated by different actors as well as the disciplines that deal with the issue, in an attempt to problematize certain assumptions that are invisible but are an important part in the production of truth. Historical background will be presented that has led to talk today of attention deficit disorder and research history focused on the production of knowledge from the Educational Intervention on the subject. Mention will be made of different perspectives that address the problem, its foundation from a biologistic, educational paradigm. It will also problematize the psychological perspective and its subdisciplines, -cognitive and social-community- the approach will depend on the theoretical framework in which it is thought. The pedagogical perspective in the present work will be focused on the perception of the disorder, being of vital importance the figure of the teacher as the first person to question certain manifestations. At present, institutions such as the school and the family that produce modern childhood, as well as the multidisciplinarity established by Neuroscience and focused on childhood, allow didactic strategies to be established to address these issues of collective interest. The heterogeneous problem is clear as a final product; This heterogeneity means that each time the problem is approached from a particular perspective, the child is solely responsible for it. Keywords: childhood, medicalización, ADHT